The impact of food quality and its attributes on customer satisfaction and behavioral intentions at Malay restaurants / Muhammad ‘Arif Aizat Bashir - Aizat Bashir, Muhammad ‘Arif (2013)
The foodservice business today is a complex and fast-changing industry. This can clearly be seen from the assortment of foodservice establishments escalating in all subsectors of the industry, including restaurants. Food quality appears to be acknowledged as an elemental factor to satisfy restaurant customers; yet, most restaurant quality-related studies have focused on atmospherics and service delivery, often neglecting the significance of food itself as the foundation of a restaurant. The primary objective of this study was to investigate how food quality is perceived in relation to satisfaction and post-dining behavioral intentions in Malay restaurants. This study also attempted to identify which attributes among food related qualities are critical in improving satisfaction and heightening revisit intention. Through regression analyses, this study shows that overall food quality significantly affects customer satisfaction and behavioral intentions and also revealed that the relationship between food quality and behavioral intentions is partially mediated by customer satisfaction. Subsequent regression analyses demonstrated that food taste was the greatest contributor to customer satisfaction; on the other hand, food freshness was the utmost contributor to behavioral intentions. Thus, restaurant operators should pay attention to the key food quality attributes that elicit customer satisfaction and enhance return visits in the restaurant business.